Skala Likert, Bias Penggunaan dan Jalan Keluarnya - Simamora, Bilson (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Many researchers refer to any graded scale as a Likert scale. In addition to misnaming, this assumption can lead to errors in the data scale and analysis technique. This paper aims to explain the instrument scales in the survey and the data types they generate. Thus, the position of the Likert scale compared to other measurement scales becomes apparent so that researchers can give the right name to the scale they use and choose the proper data analysis technique according to its type.